Chemotherapy-Associated Changes of Histopathological Features of Mycobacterium ulcerans Lesions in a Buruli Ulcer Mouse Model - Ruf, Marie-Thérèse (American Society for Microbiology, 2012)
Combination chemotherapy with rifampin and streptomycin (RIF-STR) for 8 weeks is currently recommended by the WHO as the first-line treatment for Mycobacterium ulcerans infection (Buruli ulcer). To gain better insight into the mode of action of these antibiotics against established M. ulcerans infection foci and to characterize recovery of local immune responses during chemotherapy, we conducted a detailed histopathological study of M. ulcerans-infected and RIF-STR-treated mice. Mice were inoculated with M. ulcerans in the footpad and 11 weeks later treated with RIF-STR. Development of lesions during the first 11 weeks after infection and subsequent differences in disease progression between RIF-STR-treated and untreated mice were studied. Changes in histopathological features, footpad swelling, and number of CFU were analyzed. After inoculation with M. ulcerans, massive infiltrates dominated by polymorphonuclear leukocytes developed at the inoculation site but did not prevent bacterial multiplication. Huge clusters of extracellular bacteria located in large necrotic areas and surrounded by dead leukocytes developed in the untreated mice. Chemotherapy with RIF-STR led to a rapid drop in CFU associated with loss of solid Ziehl-Neelsen staining of acid-fast bacilli. Development of B-lymphocyte clusters and of macrophage accumulations surrounding the mycobacteria demonstrated the resolution of local immune suppression. Results demonstrate that the experimental M. ulcerans mouse infection model will be a valuable tool to investigate efficacy of new treatment regimens and of candidate vaccines.